Exceptional case of a granuloma faciale with extrafacial involvement - Rada G. Shpiliyuk; Olga V. Antonova; Irena E. Belousova; Aleksey V. Samtsov (State Scientific Center of Dermatovenereology and Cosmetology, 2020)
The description of obsevation of rare dermatosis granuloma faciale is presented. Modern view about etiology, clinical picture, pathogenesis of GF is mentioned. Modern ways of treatment are considered.